(untitled) (REMUNOM, 2025)
This study analyzes the use of the literary genre of fantasy in primary education, focusing on its application in 5th grade classrooms. It investigates how teachers work with fantasy stories and their impacts on encouraging reading, as well as the social and critical development of students. Based on a quantitative approach, questionnaires were applied to teachers to identify pedagogical practices and perceptions about the benefits of the genre. Fantasy, by stimulating imagination and critical thinking, enhances engagement with reading and the development of interpretative skills. The study advocates for the inclusion of this genre in the school curriculum as a tool for fostering more meaningful learning and contributing to discussions on innovative pedagogical strategies in literature.